Oliver & company [videorecording (DVD)] - Redford, J. A. C. (Disney DVD., 2009)
Oliver is a homeless kitten who roams the streets of New York City. There, he is taken in by a gang of homeless mutts who survive by stealing from others. During one of these criminal acts, Oliver meets a wealthy young girl named Jenny Foxworth. This meeting will forever change his life.